Dialogue of Portuguese Students’ Conceptions of Significance with the Contributions of Peter Seixas - Gago, Marília (2024)
This research study aims to investigate how 12th-grade Portuguese students, concluding their compulsory education, attribute historical significance to events and historical agents in the history of Portugal over the last 100 years. Data was collected using open-ended questions, analyzed through an inductive way inspired by the categorization and analysis methods proposed by Grounded Theory, in line with research studies in History Education. The students presented various types of attribution of significance, with Causal significance and Standard significance being the most prevalent categories. These findings suggested a 3-level model of ideas, with Level 2 - Emerging contextual significance with single or multiple attribution types of Contemporary and Causal being the most frequent level encountered, followed by Level 3 - Emerging contextual significance with single or multiple attribution types of Standard and Current.